Kinetics Modelling of Tributyltin Toxicity on The Growth of Bacillus stearothermophilus (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2020)
The growth of the bacterium, Bacillus stearothermophilus was intensely inhibited by tributyltin (TBT). As the TBT concentration increases, the overall specific growth rate was inhibited. The growth rates obtained were then modelled according to the modified Han-Levenspiel, Wang, Liu, Shukor and modified Andrews. Among the five models, Wang shows the best fitting while the Andrew model shows poor fitting. Results of the statistical analysis showed that the Wang model was the best model based on the lowest values for RMSE and AICc, highest adjusted correlation coefficient (AdR2) and values of AF and BF closest to unity. The parameters obtained from the Wang model, which are Ccrit, Î¼max and m which represent critical TBT concentration (nM), maximum growth rate (nM h) and empirical constant values were 177.99 (95%, confidence interval 144.26 to 211.71), 2.41 (95%, confidence interval of 2.17 to 2.64) and 2.76 (95%, confidence interval of 1.44 to 4.07) respectively.
Keywords: Tributyltin, Toxicity, Bacillus stearothermophilus, Kinetics